Studying of physicochemical properties of newly synthesized uracil derivatives - Jadranka A. Tot; Aleksandar D. Marinković (Zaštita Materijala)
Uracil derivatives are potentially biologically active compounds, so the investigation of their physical and chemical properties is very important for their further application. In this work a series of newly synthesized derivatives of uracil was investigated by applying the spectrophotometric method. The absorption spectra were recorded in seventeen solvents with different properties. The effect of solvent was interpreted by Kamlet-Taft solvatochromic model. The dominance and the types of interactions that occur between the investigated derivatives and solvent were interpreted by applying the multiple linear correlation obtained values of absorption maxima and Hansen's solvent parameters. In addition to the effect of solvent, the influence of substituents in the molecule on absorption spectra was studied by applying Hammett equation.